The International Skin Spectra Archive (ISSA): a multicultural human skin phenotype and colour spectra collection - Yan Lu; Kaida Xiao; Michael Pointer; Ruili He; Sicong Zhou; Ahmed Nasseraldin; Suchitra Sueeprasan; Cheng Gao; Changjun Li; Ali Sohaib; Yuanyuan He; Yoko Mizokami; et al. (Scientific Data)
Abstract This paper presents the International Skin Spectra Archive (ISSA), a multicultural human skin phenotype dataset, containing 15,256 records of both spectral and colorimetric data derived from 2,113 subjects. These measurements, collected between 2012 and 2024, come from eleven different datasets gathered by international laboratories across eight countries, all adhering to a uniform measurement protocol to ensure data consistency. The ISSA dataset addresses the inherent challenges in measuring human skin colour due to its complex structure and covers a wide variability in skin characteristics such as geography, ethnicity, age, gender, and body location. Providing a broad spectrum of human skin data, the ISSA dataset will advance our understanding of skin colour variations and their biological, cultural, and environmental influences. It will also serve as a crucial resource for scientific research and technological development across various fields where diverse and precise spectral and colour data of real human skin are essential.